2016
DOI: 10.1080/17405629.2016.1205975
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between declarative pointing and theory of mind abilities in 3- to 4-year-olds

Abstract: The current study explored the relationships between declarative pointing and theory of mind abilities in 30 children between 3 and 4 years of age. Measures used to examine theory of mind (ToM) included a parental questionnaire and the Scaling of Theory of Mind Tasks. Results showed a dissociation between expressive and informative pointing, which have been regarded as two subcategories of the declarative function. ToM abilities were significantly related to the production of informative pointing, but not to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Showing, offering, and declarative pointing have all been reported in systematic studies of ape communication (e.g., Hyatt & Hopkins, 1998;Lyn et al, 2011;Russell et al, 1997); thus, declarative communication is characteristic of apes. Cochet et al (2017) found no significant relationship between declarative-expressive pointing and the development of theory-of-mind capacities in 3-4-year-old children. The idea that declarative pointing indicates that the signaler is representing the contents of others' minds is unverifiable-there is nothing that an observer can objectively measure to confirm or disconfirm the hypothesis that a creature represents others' minds while they point (Leavens et al, 2019).…”
Section: Box 1 Declarative Pointing Is Cognitively Simplementioning
confidence: 56%
“…Showing, offering, and declarative pointing have all been reported in systematic studies of ape communication (e.g., Hyatt & Hopkins, 1998;Lyn et al, 2011;Russell et al, 1997); thus, declarative communication is characteristic of apes. Cochet et al (2017) found no significant relationship between declarative-expressive pointing and the development of theory-of-mind capacities in 3-4-year-old children. The idea that declarative pointing indicates that the signaler is representing the contents of others' minds is unverifiable-there is nothing that an observer can objectively measure to confirm or disconfirm the hypothesis that a creature represents others' minds while they point (Leavens et al, 2019).…”
Section: Box 1 Declarative Pointing Is Cognitively Simplementioning
confidence: 56%
“…Deictic gestures indicate a referent and are thus contingent upon the immediate context, such as pointing to, showing, or holding out a hand to ask for an object. Deictic gestures emerge early ontogenetically, around 8 to 10 months, and are those gestures which are most typically discussed and observed in research regarding different motivations or communicative intentions behind gestures (e.g., Behne, Liszkowski, Carpenter, & Tomasello, 2012;Cameron-Faulkner, Theakston, Lieven, & Tomasello, 2015;Cochet, Jover, Rizzo, & Vauclair, 2016;Ramenzoni & Liszkowski, 2016). Bates, Camaioni, and Volterra (1975) were among the first to record the development of children's gesture use in detail.…”
Section: Gesture and Joint Attentionmentioning
confidence: 99%
“…Declarative informative pointing seems to share several characteristics with language, by both contributing to and reflecting (1) the understanding of others' attentional and knowledge states (Meng & Hashiya, 2014) and (2) the development of cooperation abilities (e.g., Brownell, Ramani, & Zerwas, 2006;Liszkowski, 2005). In addition, theory of mind abilities (ToM), measured with standard tasks (e.g., Sally-Ann test) in children between 3 and 4 years of age, appear to be significantly related to the production of informative pointing, but not to the production of expressive pointing (Cochet, Jover, Rizzo, & Vauclair, 2016). Although little is known about the role of informative pointing at earlier stages of development, the production of this gesture during toddlerhood might be closely associated with the development of language and ToM.…”
mentioning
confidence: 99%